1996
DOI: 10.1002/(sici)1097-4644(19960601)61:3<459::aid-jcb13>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian CAP interacts with CAP, CAP2, and actin

Abstract: We previously identified human CAP, a homolog of the yeast adenylyl cyclase-associated protein. Previous studies suggest that the N-terminal and C-terminal domains of CAP have distinct functions. We have explored the interactions of human CAP with various proteins. First, by performing yeast two-hybrid screens, we have identified peptides from several proteins that interact with the C-terminal and/or the N-terminal domains of human CAP. These peptides include regions derived from CAP and BAT3, a protein with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…pLexA-⌬PHD and pLEXA-PHD were generated by inserting codons 1 to 222 and 222 to 282, respectively, of YNG2 into pBTM116. pADHA-Yng2, pADHA-Png1, and pADHA-Ing1 were generated by cloning the PCR-derived open reading frame (ORF) of YNG2, S. pombe PNG1, or human p33 ING1 respectively, into pAD4.H, which contains the 2m origin of replication and ADH1 promoter (32). YEp-PDE2 contains S. cerevisiae PDE2 in YEp13, as previously described (65).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…pLexA-⌬PHD and pLEXA-PHD were generated by inserting codons 1 to 222 and 222 to 282, respectively, of YNG2 into pBTM116. pADHA-Yng2, pADHA-Png1, and pADHA-Ing1 were generated by cloning the PCR-derived open reading frame (ORF) of YNG2, S. pombe PNG1, or human p33 ING1 respectively, into pAD4.H, which contains the 2m origin of replication and ADH1 promoter (32). YEp-PDE2 contains S. cerevisiae PDE2 in YEp13, as previously described (65).…”
Section: Methodsmentioning
confidence: 99%
“…This PCR product was cloned into pADGFPHA-Yng2 as an EcoRI/SacI fragment to replace the C-terminal PHD finger of Yng2 with that of Yng1. pADmyc-Yng2 was generated by cloning the PCR-derived ORF of YNG2 in pUAD6 (32). pADmyc-Tra1 was derived by shuttling the TRA1 ORF as a NotI(filled-in)/SacI fragment from p1259 (a kind gift from C. Brandl) into the SmaI/SacI sites of a modified pUAD6 (SalI digested, filled in, and religated).…”
Section: Methodsmentioning
confidence: 99%
“…1C). Furthermore, a study, in which short CAP fragments where used, suggests that the N-terminal part of CAP can bind to both the N-terminal and C-terminal sections of a second CAP (Hubberstey et al, 1996). A mutational study of Dictyostelium CAP suggests that several configurations of a CAP dimer are possible (Yusof et al, 2006).…”
Section: Oligomerization Of Cap and Its Effect On Actin Regulationmentioning
confidence: 99%
“…CAP also binds monomeric actin and, therefore, also possesses a cytoskeletal function (11 -15). However, only a few studies about CAP have previously been reported in mammalian cells (16) and no studies about CAP in human cancer have been published. In the present study, we have investigated the expression of CAP2 and proved its overexpression in multistage carcinogenesis in HCC.…”
mentioning
confidence: 99%